Rwandan perceptions of jews, judaism, and Israel - Beloff, Jonathan R. (Journal of religion in Africa, 2022)
Religious studies of Rwanda typically focus on Christianity’s involvement before, during, and after the 1994 Genocide against the Tutsi, also referred to as the Rwandan Genocide. Rwanda’s postgenocide reconstruction has witnessed new and changing political and social commitments by previously established religious organisations such as the Roman Catholic, Protestant, and Adventist Churches. The Rwandan government has taken a more progressive stance on divisions of power and religious institutions, and the promotion of religious freedoms that has benefitted the domestic Muslim population. This essay examines how Judaism, a previously unknown religion in the region, is impacting Rwandan identity formation. Jewish identity is increasingly being tied to the nation’s own reconstructed identity, with a strong focus on historical persecution, rebuilding after genocide, and development. This essay suggests that Rwandan identity and religious studies should include the ever-growing ties with Jews and Israel to better understand its political and social reconstruction since 1994.